Liver Transplantation for Alcohol-Related Liver Disease (ARLD): An Update on Controversies and Considerations - Dipesh Kumar Yadav; Qi Zhang; Xueli Bai; Enliang Li; Tingbo Liang (Canadian Journal of Gastroenterology and Hepatology)
According to the recent data from the United Network for Organ Sharing database, alcohol-related liver disease (ARLD) accounts to be the most common indication of liver transplantation (LT) waiting lists in the United States among men without hepatocellular carcinoma (HCC). Severe alcoholic hepatitis (AH) is serious and the life-threatening form of ARLD and should be treated timely. However, the LT for severe AH remained to be controversial among the transplant community because of marked interests about the constrained organ supply and the hazard that the AH liver recipient will return to risky drinking. Early LT for ARLD refers for a patient with severe AH undergoing LT who are non-responder to medical treatments. These patients are generally on the existing waiting list but usually followed by 6-month duration of alcohol abstinence. However, the rule of 6-month alcohol abstinence need before the LT is ambiguous. The 6-month alcohol abstinence was consistently defended in light of the compelling fact that it would enable patients to recoup from the intense impacts of alcohol to the liver. In routine, however, the purported “6-month abstinence rule” turned into a surrogate for the forecast of future drinking by ARLD patients for the LT. Careful consideration should be given to the alcohol use disorder of craving and the hazard for recidivism after the LT. As for the current situation, there, urgently, is a specific need of standardized criteria for the evaluation of patients with severe AH for earlier LT. Moreover, further studies are required precisely to develop an accurate prediction model for posttransplant alcohol recidivism. Additionally, development of a standardized protocol for post-LT follow-up and management is further needed. We carefully outlined the published experience with the LT for ARLD in this review.